Examining the Usefulness and Ease of Learning Management Systems: A Mixed Methods Study of Student Perspectives - Linda, Khoo Mei Sui; Nurlisa, Loke Abdullah; B., Subatira; Wan Sofiah, Meor Osman (Human Resource Management Academic Research Society (HRMARS), 2025)
Learning Management Systems (LMS) are fundamental to contemporary education, serving as platforms that help students organise and enhance their academic pursuits. This mixed methods research involved surveying 528 undergraduates to assess if LMS platforms align with their educational objectives and to explore the relationship between student-focused instructional strategies and LMS effectiveness. Results indicate that the majority of students view the LMS as an important asset for supporting their academic performance. These findings affirm the LMS’s role in facilitating student achievement and provide actionable insights for universities seeking to implement effective digital solutions. Additionally, the outcomes offer valuable considerations for higher education institutions choosing suitable LMS platforms for their student populations and for designers developing comprehensive assessment features.